Efficiency Of Beef Cattle Supply Chain Management Using Digital Marketing - Hasanah, Niswatin; Prasetyo, Budi; Nurkholis, Nurkholis; Fitri, Zilvanhisna Emka; Riansyah, S; Sono, S. H; Prihatiana, D; Wahyono, Nanang Dwi; Haryuni, N (P3M Politeknik Negeri Jember, 2025)
This study aimed to analyze the efficiency of beef cattle supply chain management in Jember Regency during and after the Eid al-Adha period, and to evaluate the role of digital marketing in improving distribution. The research was conducted in July 2024 using a survey method with purposive sampling for selecting farmers and snowball sampling for marketing institutions. The results showed three marketing patterns: Pattern I (Producers directly to consumers using the “SAPI SIP” digital platform), Pattern II (Producers – Wholesalers – Agents outside the city/province), and Pattern III (Producers – Wholesalers – Religious institutions – Consumers). The most efficient marketing pattern during the Eid al-Adha period was Pattern I, with the highest farmer price share: 95.24% for male cattle and 94.29% for female cattle. This was due to the direct-to-consumer approach via digital marketing, which reduced intermediaries and transaction costs. After Eid al-Adha, Pattern I remained the most efficient for male cattle (88.00%), while Pattern III showed slightly higher efficiency for female cattle (90.17%) due to strong institutional buyer networks. These findings indicate that digital marketing can significantly improve supply chain efficiency and enhance farmer welfare, especially during seasonal demand surges.